Assessing Entrepreneurial Potential of University: Empirical Evidence from Croatia - Oberman Peterka, Suncica; Mezulic Juric, Petra; Koprivnjak, Tihana (Marketing & Menedzsment, 2017)
AIMS OF THE PAPER This paper deals with the main characteristics of entrepreneurial university and uses the cases of two Croatian universities to demonstrate how far they are from being entrepreneurial. The question arises, to what extent did these two Croatian universities adapt to the new circumstances and how close are they to fulfilling their third mission and becoming entrepreneurial. METHODOLOGY This paper compares two Croatian public universities according to characteristics of entrepreneurial university, developed by Ranga (2014) and will try to see how similar or different they are, what is missing and what can be done in order for them to become more entrepreneurial. MOST IMPORTANT RESULTS The change process is long and difficult and there is no unique solution how to transform a university into an entrepreneurial university; each university has to find its own specific pathways, its own specific configuration how to bring about change that is reflected by situation, resources and environment in which each university operates (Clark,2004). Analyses of these universities show that some elements of entrepreneurial universities exist at both universities but they are not systematically developed and usually not part of strategic plans of the universities. RECOMMENDATIONS This paper gives recommendations of what is missing and what needs to be done in order to become an entrepreneurial institution. Universities need to find a way to act more innovatively to create a more engaging environment for researchers and students, and to collaborate with their stakeholders. In order to achieve this, they need to become entrepreneurial organizations. Universities should not focus just on transferring knowledge to students or producing new knowledge, but also on implementation and usage of that knowledge in solving the problems of industry and society in which they operate.